Integration of mathematical models for ore mining industry. Issue 1 (2nd January 2019) - Liu, Shi Qiang; Kozan, Erhan
ABSTRACT: This paper investigates the integration of planning and scheduling theory for open-pit ore mining industry under comprehensive mining constraints and attributes. Consequently, mine design planning, mine block sequencing and mine production scheduling problems are modelled, solved, interacted and integrated in a whole system. A series of interrelated mixed integer programming models and hybrid solution approaches are developed. Based on a real-world case study, it is validated that the integration of mathematical models is promising to significantly improve the overall efficiency of mining management in an analytical way.